2015
DOI: 10.1017/s0950268815002228
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms cannot predict influenza infection during the 2013 influenza season in Bavaria, Germany

Abstract: For influenza surveillance and diagnosis typical clinical symptoms are traditionally used to discriminate influenza virus infections from infections by other pathogens. During the 2013 influenza season we performed a multiplex assay for 16 different viruses in 665 swabs from patients with acute respiratory infections (ARIs) to display the variety of different pathogens causing ARI and to test the diagnostic value of both the commonly used case definitions [ARI, and influenza like illness (ILI)] as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…We believe that different results mainly existed because of different geographical regions and different characteristics of H1N1 infection. On the other hand, our findings agreed with those from a German study reporting that clinical symptoms could not predict influenza infection [25]. Interestingly, analogous to our study, abnormal CRP was the most sensitive screening tool for influenza in a recent study from an ambulatory stem-cell transplant center during an influenza outbreak [26].…”
Section: Discussionsupporting
confidence: 92%
“…We believe that different results mainly existed because of different geographical regions and different characteristics of H1N1 infection. On the other hand, our findings agreed with those from a German study reporting that clinical symptoms could not predict influenza infection [25]. Interestingly, analogous to our study, abnormal CRP was the most sensitive screening tool for influenza in a recent study from an ambulatory stem-cell transplant center during an influenza outbreak [26].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the symptoms of influenza, it is still a problem to try to make an assertive diagnosis based solely on clinical symptoms. In a study conducted in Germany, they found that only 44% of confirmed cases were suspected to be influenza by physicians when they were guided by the definition of ILI [ 37 ]. In our work, we observed that some of the symptoms most associated with influenza-positive cases were arthralgias, myalgias, conjunctivitis, fever and headaches, while negative cases were those most associated with cyanosis, polypnoea, dyspnoea and prostration.…”
Section: Discussionmentioning
confidence: 99%
“…We used the recommended definitions for RTI surveillance in geriatric units, divided in 3 subcategories: (i) common cold syndromes or pharyngitis (at least two of the following criteria: runny nose or sneezing, stuffy nose (i.e. congestion), sore throat or hoarseness or difficulty swallowing, dry cough, swollen or tender glands in the neck (cervical lymphadenopathy)), (ii) influenza-like illness (both the following criteria must be met: fever AND at least three other symptoms (chills, new headache or eye pain, myalgia or body aches, malaise or loss of appetite, sore throat, new or increased dry cough)) and (iii) lower respiratory tract infection (both of the following criteria must be met: at least two respiratory signs or symptoms (new or increased cough, new/increased sputum production, O 2 saturation <94% or reduced >3% from baseline, abnormal lung examination (new or changed), pleuritic chest pain, respiratory rate �25 breaths/min AND one or more constitutional signs/symptoms (fever, leukocytosis, confusion, acute functional decline)) [13][14][15][16]. Infection corresponding to one of these three subcategories was included in this study and classified as RTI.…”
Section: Case Inclusion and Lethality Studymentioning
confidence: 99%